PENGARUH CORPORATE SOCIAL RESPONSIBILITIES DAN LIKUIDITAS TERHADAP EARNING RESPONSE COEFFICIENT DENGAN STRUKTUR MODAL SEBAGAI VARIABEL MODERASI - Tasya Tasya (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2020)
The purpose of this research is to find the effect of Corporate Social Responsibilities and Liquidity on Earning Response Coefficient with Capital Structure as a moderating variable. The sample in this research uses companies in the Mining sector for the period of 2016 – 2018. The criteria in determining the sample of this research are companies listed on the IDX, have The criteria in determining this research sample are companies listed on the IDX, have a complete annual report and CSR disclosure in the 2016 – 2018 period. From these criteria found 63 samples for research. In brief, the results of this research explained that Corporate Social Responsibilities and Liquidity have no significant effect on Earning Response Coefficient, and also Capital Structure can’t moderate the relationship between Corporate Social Responsibilities and Liquidity on Earning Response Coefficient.